Tranilast Suppresses the Disease Development of the Adjuvant- and Streptococcal Cell Wall-Induced Arthritis in Rats - Toshiaki Nagate; Toru Tamura; Fumiyasu Sato; Junji Kuroda; Jun Nakayama; Nobuo Shibata (Elsevier, 2007)
This study explores the effects of the anti-allergic and anti-fibrotic agent tranilast on adjuvant- and streptococcal cell wall-induced arthritis in rats, animal models of rheumatoid arthritis in humans. Tranilast (150 or 300 mg/kg, twice daily) or vehicle only was administered orally to the two arthritis models, from 17 days before sensitization. As a comparative control, methotrexate (0.1 mg/kg, once daily) was given to another group. Tranilast suppressed the increase in foot volumes, paw thicknesses, clinical scores, and histopathological scores of the ankle joints in both models dose-dependently. In addition, the fibrosis indices of the ankles were dramatically decreased by tranilast in both of the models. Compared to the effects of methotrexate, tranilast seemed to work more effectively in the streptococcal cell wall-induced arthritis model than in the adjuvant-induced arthritis model. From these observations, it can be concluded that tranilast suppresses the development of arthritis in multiple models and is potentially a novel therapeutic agent for human rheumatoid arthritis. Keywords:: tranilast, rheumatoid arthritis, adjuvant-induced arthritis, streptococcal cell wall-induced arthritis, methotrexate